Belief in Saints. Sensory Reality in Religious Experience (As presented in Examples from Croatia) - Belaj, Marijana (Array, 2007)
Examples of people’ s belief in patron saints on the territory of Croatia are used in an attempt to explain the sensation of sanctity through the prism of the senses harnessed in its shaping. In the same context, some practices noticed during a contemporary celebration of the Youth Day (the birthday of Josip Broz Tito) in Kumrovec point to the process of consecrating of the person and place that normally, due to their provenance, are marked as absolutely non-religious or even anti-religious.